CD74 ablation rescues type 2 diabetes mellitus-induced cardiac remodeling and contractile dysfunction through pyroptosis-evoked regulation of ferroptosis. (February 2022) - Chen, Lin; Yin, Zhiqiang; Qin, Xing; Zhu, Xiaoying; Chen, Xu; Ding, Gangbing; Sun, Dong; Wu, Ne N.; Fei, Juanjuan; Bi, Yaguang; Zhang, Jingjing; Bucala, Richard; et al.
Abstract: Type 2 diabetes mellitus (T2D) contributes to sustained inflammation and myopathic changes in the heart although the precise interplay between the two remains largely unknown. This study evaluated the impact of deficiency in CD74, the cognate receptor for the regulatory cytokine macrophage migration inhibitory factor (MIF), in T2D-induced cardiac remodeling and functional responses, and cell death domains involved. WT and CD74 -/- mice were fed a high fat diet (60% calorie from fat) for 8 weeks prior to injection of streptozotocin (STZ, 35 mg/kg, i.p., 3 consecutive days) and were maintained for another 8 weeks. KEGG analysis for differentially expressed genes (DEGs) reported gene ontology term related to ferroptosis in T2D mouse hearts. T2D patients displayed elevated plasma MIF levels. Murine T2D exerted overt global metabolic derangements, cardiac remodeling, contractile dysfunction, apoptosis, pyroptosis, ferroptosis and mitochondrial dysfunction, ablation of CD74 attenuated T2D-induced cardiac remodeling, contractile dysfunction, various forms of cell death and mitochondrial defects without affecting global metabolic defects. CD74 ablation rescued T2D-evoked NLRP3-Caspase1 activation and oxidative stress but not dampened autophagy. In vitro evidence depicted that high glucose/high fat (HGHF) compromised cardiomyocyte function and promoted lipid peroxidation, the effects were ablated by inhibitors of NLRP3, pyroptosis, and ferroptosis but not by the mitochondrial targeted antioxidant mitoQ. Recombinant MIF mimicked HGHF-induced lipid peroxidation, GSH depletion and ferroptosis, the effects of which were reversed by inhibitors of MIF, NLRP3 and pyroptosis. Taken together, these data suggest that CD74 ablation protects against T2D-induced cardiac remodeling and contractile dysfunction through NLRP3/pyroptosis-mediated regulation of ferroptosis. Graphical Abstract: ga1